Conclusion on the peer review of the pesticide risk assessment of the active substance topramezone - European Food Safety Authority (EFSA Journal, 2014)
The conclusions of the European Food Safety Authority (EFSA) following the peer review of the initial risk assessments carried out by the competent authority of the rapporteur Member State France, for the pesticide active substance topramezone are reported. The context of the peer review was that required by Commission Regulation (EU) No 188/2011. The conclusions were reached on the basis of the evaluation of the representative use of topramezone as a herbicide on maize. The reliable endpoints concluded as being appropriate for use in regulatory risk assessment, derived from the available studies and literature in the dossier peer reviewed, are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are identified that the potential for groundwater exposure above the parametric drinking water limit of 0.1µg/L that applies to pesticide active substances and their relevant metabolites, was assessed as high in the vulnerable groundwater situations, that are represented by the geoclimatic conditions of all 8 pertinent FOCUS groundwater scenarios and a high long-term risk to mammals is indicated with the available data.